FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN UMKM PADA MASA PANDEMI COVID-19 - Dedi Damhudi; Tri Lestari; Faizal Roni (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
During the pandemic of COVID-19, many businesses have been falling and have a declining revenue. By gathering information samplings through online surveys consisted of thirty-two respondents and the usage of Chi-square quantitative analysis data method, the study was conducted by finding out its effect on income during the pandemic. The independent variables consisted of business income before the pandemic, the loans, and the BPUM used to see the correlation with the dependent variable. The findings show that the independent variables had a statistically significant influence on the dependent variable in parallel.